2022
DOI: 10.32598/sija.2021.593.4
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship Between Social Support, Cognitive Status, and Depression With Daily Life Activities of the Elderly in Amirkola City

Abstract: Objectives The rapid growth of the elderly population has led to more problems, such as declining independence. Due to the importance of doing independent daily living activities in the elderly, this study was conducted to determine the relationship between social support, cognitive status, and depressive symptoms with daily activities in the elderly in Amirkola City. Methods & Materials This matched case-control study is part of the first phase of the cohort project for the elderly in Amirkola City, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The findings of Khodadadi et al 's study on cognitive status showed that the average cognitive status of elderly people who were unable to perform daily life activities was significantly higher than that of people who were unable to perform daily life activities. Also, the results indicated that the chance of cognitive impairment was higher in the elderly with the inability to perform daily life activities [28].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The findings of Khodadadi et al 's study on cognitive status showed that the average cognitive status of elderly people who were unable to perform daily life activities was significantly higher than that of people who were unable to perform daily life activities. Also, the results indicated that the chance of cognitive impairment was higher in the elderly with the inability to perform daily life activities [28].…”
Section: Discussionmentioning
confidence: 95%
“…The range of scores of this questionnaire varies from 12 to 48. According to the scores they get in the questionnaire, people are classified into three categories: poor (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), average (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), and good (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). Therefore, earning more points means a better quality of life.…”
Section: Measurementmentioning
confidence: 99%
“… 56 According to the previous study, the most important feature of depression is mood swings, which can lead to disability in performing ADLs among older adults. 20 Furthermore, Boga and Saltan reported that the levels of dependence on activities in daily living were related to mental status and depression among older adults. In addition to the financial cost, depression in older adults has negative consequences.…”
Section: Discussionmentioning
confidence: 99%
“… 1 This is because depression in older people can be reduced by performing ADLs. 20 According to Storeng et al, the most significant risk variables for needing assistance with one or more basic/instrumental daily living activities were life satisfaction, depression, and health perception. These elements can be among the potential targets for preventative measures.…”
Section: Discussionmentioning
confidence: 99%
“…One of the important challenges of older adults is the disability to perform daily life activities, and the physical limitation [ 19 ]. Due to the importance of daily independent living activities for older adults, unfortunately, they face more problems, including a decrease in independence [ 20 ]. A review of the literature showed that one-quarter of people, after reaching retirement age cannot do their activities [ 21 ], which may affect sleep quality [ 19 ].…”
Section: Introductionmentioning
confidence: 99%